2009
DOI: 10.3389/neuro.07.020.2009
|View full text |Cite
|
Sign up to set email alerts
|

A brain-machine interface instructed by direct intracortical microstimulation

Abstract: Brain–machine interfaces (BMIs) establish direct communication between the brain and artificial actuators. As such, they hold considerable promise for restoring mobility and communication in patients suffering from severe body paralysis. To achieve this end, future BMIs must also provide a means for delivering sensory signals from the actuators back to the brain. Prosthetic sensation is needed so that neuroprostheses can be better perceived and controlled. Here we show that a direct intracortical input can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 37 publications
5
118
1
5
Order By: Relevance
“…Early examples of somatosensory neuroprostheses demonstrated that animals could perform behavioural tasks based on largely arbitrary patterns of ICMS delivered to S1 [17][18][19][20]. These studies applied Romo's finding-that animals could discriminate ICMS that varied in frequency-to establish a proof-of-principle that this approach might be applied to bi-directional brain-machine interfaces-i.e.…”
Section: The Birth Of Somatosensory Neuroprosthesesmentioning
confidence: 99%
“…Early examples of somatosensory neuroprostheses demonstrated that animals could perform behavioural tasks based on largely arbitrary patterns of ICMS delivered to S1 [17][18][19][20]. These studies applied Romo's finding-that animals could discriminate ICMS that varied in frequency-to establish a proof-of-principle that this approach might be applied to bi-directional brain-machine interfaces-i.e.…”
Section: The Birth Of Somatosensory Neuroprosthesesmentioning
confidence: 99%
“…Studies that use electrical stimulation to evoke complex motor movements use less, with typical values being 300 Hz, 500 ms, and amplitudes ranging from 10 to 300 A depending on cortical area (Bruce et al 1985;Graziano et al 2002;Thier and Andersen 1998). Finally, awake behaving studies have found current detection thresholds to be around 10 A, or less with training, when intracortical microstimulation is applied to sensory cortices (Medina et al 2012;Murphey and Maunsell 2007;Ni and Maunsell 2010;O'Doherty et al 2009;Salzman et al 1990; for reviews, see Clark et al 2011;Histed et al 2013). For the parameters tested, cortical activation was dependent on both the current amplitude of a single pulse and the number of pulses.…”
Section: Effects Of Stimulation Parametersmentioning
confidence: 99%
“…Figure 3 shows the schematics of the first brain-computer-brain interface (BCBI) designed in Nicolelis laboratory by O'Doherty, Lebedev and their colleagues [80]. Microelectrode arrays were implanted into motor and somatosensory cortex of monkeys.…”
Section: Bidirectional Bcis (Brain-computer-brain Interface)mentioning
confidence: 99%
“…The sensory part of the loop serves as a feedback tool. It transmits artificial tactile signals into somatosensory cortex through intracortical microstimulation (O'Doherty et al [80]). Integration of brain activity of several subjects using a brain net Each monkey was seated in a separate room and watched a virtual arm on the screen; the task was to touch the object using the virtual arm (A).…”
Section: обзор нейроинтерфейсыmentioning
confidence: 99%